Scoring system for early detection in pulmonary hypertension type I based on clinical presentation, electrocardiography, and chest X-ray at RSUD dr. Saiful Anwar - Galuh, Lukitasari Ayu; Martini, Heny; Rahimah, Anna Fuji (Universitas Brawijaya, 2024)
Background: In Indonesia, pulmonary hypertension prevalence is 1:10.000 population. Due to its atypical symptoms, often PH patients come as a late presenters thus they have a worse prognosis. The golden standard to diagnose is Right Heart Catheterization (RHC) which is not widely available.Objectives: To generate a scoring system based on clinical presentation, electrocardiogram, and chest x-ray for early detection.Methods: A hospital-based cross-sectional survey was conducted in RSUD dr. Saiful Anwar, East Java from July 2020 â€“ November 2023 with data from the medical record in which all variables are obtained at one period. Data were analyzed using bivariate analysis, multiple logistic regression, and Area Under Curve (AUC) from Receiver Operating Characteristic (ROC).Results: A total of 244 patients who were above 18 years old were conducted RHC at RSUD dr. Saiful Anwar East Java. We found a total score of 12 consisting of Dyspnea on Effort (DOE) score 2, Palpitation score 1, Increasaed P2 score 2, Increased JVP (Jugular vein pressure) score 2, RV (Right Ventricular) Heaves score 2, Right bundle branch block (RBBB) score 1, and Cardiomegaly (CTR >50%) score 2. With a 2 x 2 table, we found that a score of â©¾5 is likely for pulmonary hypertension diagnosis.Conclusion: Our study is a predictive model with a scoring system that has good sensitivity and specificity in selected populations where one of its limitations is sampling bias thus cannot yet be applied to the general population and needs further research for validation.